Levels Of Depression For Postpartum Women In The Working Area Of The Makrayu Puskesmas, Palembang - Illustri Illustri (Jurnal EduHealth, 2023)
Postpartum mothers have a vulnerability to various mental disorders, one of which is postpartum depression which occurs after 6 weeks to one year after delivery which can affect the development of the baby and the role of the mother. The prevalence of postpartum depression in the world varies from 6.5% to 15% and increases every year, mostly occurring in developing countries including Indonesia. This study aims to determine the level of depression in postpartum mothers in the working area of ​​the Makrayu Public Health Center in Palembang. This research method uses a cross sectional study design with an accidental sampling technique. The sample in this study were all postpartum mothers as many as 86 respondents. Retrieval of data using the BDI version II questionnaire instrument which has been translated into Indonesian. The results showed that the level of postpartum depression in respondents varied, ranging from not depressed (minimum depression) as many as 48 respondents (56%), mild 18 respondents (21%), moderate 13 respondents (15%) and severe 7 respondents (8%) . A high risk for mothers experiencing postpartum depression occurs in mothers who have an age range of 20-34 years (82%), multiparous mothers (54%), mothers with secondary education (45%), mothers who do not work or housewives (80%) and mothers with normal types of labor experienced postpartum depression (70%). The results of this study indicate that postpartum depression is experienced by each respondent with varying levels of depression and there are risk factors that can increase the prevalence of depression.